2013
DOI: 10.1186/1556-276x-8-397
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase electrochemical reduction of graphene oxide films in alkaline solution

Abstract: Graphene oxide (GO) film was evaporated onto graphite and used as an electrode to produce electrochemically reduced graphene oxide (ERGO) films by electrochemical reduction in 6 M KOH solution through voltammetric cycling. Fourier transformed infrared and Raman spectroscopy confirmed the presence of ERGO. Electrochemical impedance spectroscopy characterization of ERGO and GO films in ferrocyanide/ferricyanide redox couple with 0.1 M KCl supporting electrolyte gave results that are in accordance with previous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 38 publications
6
24
0
Order By: Relevance
“…After reduction by electrochemical cycling, the above and absorption peaks corresponding to C−O stretching vibrations at 1060 cm −1 (for graphite), 1020 cm −1 (for GO), 1052 cm −1 (for GO/MWCNT/PyBA) almost disappeared indicating the removal of oxygenated groups from the GO and GO/MWCNT/PyBA surface and mainly the residual C−O−C groups (SI, Figure S2, red line, and Figure c). The presence of the intrinsic absorption peak of graphite appeared at 1622 cm −1 (GO) , 1611 cm −1 (ERGO) , 1607 cm −1 (GO/MWCNT/PyBA), 1608 cm −1 (ERGO/MWCNT/PyBA), confirmed the recovery of the graphite conjugated structure (1650 cm −1 ) after reduction (SI, Figure S2). Similar spectroscopic characteristics observed for pristine ERGO and ERGO/MWCNT/PyBA revealed that the presence of PyBA modified MWCNT does not influence the electrochemical reduction of GO .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…After reduction by electrochemical cycling, the above and absorption peaks corresponding to C−O stretching vibrations at 1060 cm −1 (for graphite), 1020 cm −1 (for GO), 1052 cm −1 (for GO/MWCNT/PyBA) almost disappeared indicating the removal of oxygenated groups from the GO and GO/MWCNT/PyBA surface and mainly the residual C−O−C groups (SI, Figure S2, red line, and Figure c). The presence of the intrinsic absorption peak of graphite appeared at 1622 cm −1 (GO) , 1611 cm −1 (ERGO) , 1607 cm −1 (GO/MWCNT/PyBA), 1608 cm −1 (ERGO/MWCNT/PyBA), confirmed the recovery of the graphite conjugated structure (1650 cm −1 ) after reduction (SI, Figure S2). Similar spectroscopic characteristics observed for pristine ERGO and ERGO/MWCNT/PyBA revealed that the presence of PyBA modified MWCNT does not influence the electrochemical reduction of GO .…”
Section: Resultssupporting
confidence: 90%
“…for the hybrid material in comparison to the pristine graphene oxide (SI, Figure S2). By analyzing obtained spectra, (SI, Figure S2, black line) the characteristic band for the skeletal vibration of the graphite C=C bond was observed at 1650 cm À1 [31]. In the FTIR spectra of GO (SI, Figure S2, blue line) and GO/MWCNT/PyBA (Figure 3b), originating from OÀH stretching vibrations band [29,32] (visible in graphite spectrum at 3439 cm À1 ) became stronger and broader at 3413 cm À1 and 3418 cm À1 , respectively.…”
Section: Electrochemical Reduction Of Go/mwcnt/pyba and Physicochemicmentioning
confidence: 99%
“…Electrochemical reduction of the oxygen-based functionalities from GO did not affect the morphology of the sensor surface, which presents the same crumpled and wrinkled texture. Little different morphology of RGO (obtained by electrochemical or chemical reduction) from that of its GO counterpart is also reported in the literature [17,[25][26][27][28].…”
Section: Resultsmentioning
confidence: 53%
“…Graphene, as a member of carbon family, possesses speci¯c surface area and superior electron mobility [10][11][12][13][14] which is an ideal support for anchoring nanoparticles. Recently, integrating graphene with di®erent nanoscaled materials has attracted much attention [14][15][16][17] because graphene can serve as an excellent supporting matrix for photocatalyst particles and can also e®ectively inhibit the recombination of the electron-hole pairs in the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, integrating graphene with di®erent nanoscaled materials has attracted much attention [14][15][16][17] because graphene can serve as an excellent supporting matrix for photocatalyst particles and can also e®ectively inhibit the recombination of the electron-hole pairs in the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%